Portions of the Book of Common Prayer [electronic resource] : together with hymns, addresses, etc., for the use of the Eskimo of Hudson's Bay - Church of England.; Peck, E. J. (Edmund James), 1850-1924. (London : Society for Promoting Christian Knowledge, 1881)
Electronic reproduction. Mode of access: Internet. 44